¿Cómo integrar las nuevas tecnologías en educación inicial? - Martínez, Jeanette (2011)
How to integrate new technologies into initial education?Currently, the relationship computer-children is a debate that generates still little agreement, because it is a new subject with to much to learn. This essay seeks to contribute to its thematic analysis, exposing a series of ideas and practical insights for achieving appropriate integration of new technologies at the initial level, which is a process without return. It is therefore necessary that the teachers manage key criteria to make the pedagogical decisions of the case in the exercise of its training role with the «digital natives», their students, forming the skills needed to act effectively in the new information and knowledge society. It will also be necessary as «immigrants from the virtual environment», that the teacher arise the need for training in the field of computer science to understand this new language in relation to the world of today.